The effect of dietary soybean meal level in phase I on subsequent phase II growth performance - Friesen, K.G.; Kats, L.J.; Goodband, Robert D.; Nelssen, Jim L.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred and four pigs (initially 11.7 lb and 21 d of age) were used to determine the effect dietary soybean meal has on growth performance in the early-weaned pig. Pigs were fed one of four diets from d 0 to 14 postweaning. Diets were formulated to 1.5% lysine and 24.4% lactose with either 0, 7.5, 15.0, or 22.5% soybean meal. Soybean meal and lactose replaced dried skim milk to maintain equal lysine and lactose levels. From d 14 to 35 postweaning, all pigs were fed a common (1.25% lysine) corn-soybean meal diet containing 10% dried whey and 4% select menhaden fish meal. Growth performance (ADG, ADFI, and FIG) was not influenced by dietary soybean meal level fed from d 0 to 14 postweaning. From d 14 to 35 postweaning, ADG was not influenced by dietary soybean meal level during d 0 to 14. Average daily feed intake was decreased linearly during d 14 to 35 as dietary soybean meal (d 0 to 14) increased. Conversely, feed efficiency during d 14 to 35 improved linearly as dietary soybean meal increased (d 0 to 14). Cumulative (d 0 to 35) ADG was not affected by the amount of dietary soybean meal (7.5, 15.0, or 22.5%) fed from d 0 to 14 postweaning, whereas ADFI decreased linearly and feed efficiency was improved linearly. These data suggest that soybean meal can be included in a high nutrient dense starter diet at levels up to 22.5% without impairing phase I (d 0 to 14 postweaning) growth performance and overall growth Performance. The phase I diet must contain soybean meal for optimal subsequent performance.
Keywords: Swine; Starter pigs; Soybean meal; Dried skim milk